KANDUNGAN ASAM LEMAK, ZINK, DAN COPPER PADA TEMPE, BAGAIMANA POTENSINYA UNTUK MENCEGAH PENYAKIT DEGENERATIF? - Diah M. Utari (GIZI INDONESIA, 2010)
FATTY FOOD, ZINC, AND COPPER CONTENTS IN TEMPE, HOW ITS POTENTIAL TO PREVENT DEGENERATIF DISEASES?Tempe is Indonesian traditional food that very popular, but its function has not been well informed by community. During the fermentation process, Rhizopus sp causes compositional changes in lipid, by hydrolysis more than one-third of fat of soybeans. The fatty acid composition that predominant in tempe composed by linoleic acid, oleic acid and linolenic acid. Tempe also contains minerals, namely Zn and Cu,that have role in increasing SOD antioxidant enzyme activity. The role of the enzyme is as a first barrier to free radical. Tempe could be considered as functional food which have benefit for address of lipid profile and prevent free radical which may reduce degenerative disease risk. Although there are no dietary recommendation of tempe for individual, it may a great benefit to consume tempe about 2-3 slice/day (100-150 g). It is better to cook with boiling or steaming to get maximal benefit of tempe for health.Key words: traditional food, tempe, fermentation